Image Restoration using Voronoi Diagrams - Laura-Bianca BILIUS; Stefan-Gheorghe PENTIUC (Journal of Applied Computer Science & Mathematics, 2018)
The restoration of digital images has become highly sought over time and this is why so many algorithms that promise a more optimal and undistorted outcome have appeared. This paper presents an algorithm for rebuilding missing areas in digital images. Compared to other algorithms, this assumes dividing the plane of the image into sub-regions using Voronoi diagrams.